2013
DOI: 10.1128/aac.01355-13
|View full text |Cite
|
Sign up to set email alerts
|

Isavuconazole (BAL4815) Pharmacodynamic Target Determination in an In Vivo Murine Model of Invasive Pulmonary Aspergillosis against Wild-Type and cyp51 Mutant Isolates of Aspergillus fumigatus

Abstract: Invasive pulmonary aspergillosis (IPA) continues to rise in concert with increasing numbers of immune suppression techniques to treat other medical conditions and transplantation. Despite these advances, morbidity and mortality rates remain unacceptably high. One strategy used to optimize outcomes is antifungal pharmacodynamic (PD) examination. We explored the pharmacodynamics of a new triazole in development, isavuconazole, in a murine neutropenic IPA model. Ten A. fumigatus isolates were used, including four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
65
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 37 publications
3
65
1
2
Order By: Relevance
“…However, in our previous studies with azoles, we showed that using survival as a gold standard endpoint in our model provides useful exposure-response relationships. Studies with azoles in neutropenic (27,47,48) and nonneutropenic (23,49,50) models have shown that the exposure-response relationships are of the same order of magnitude; in fact, a slightly lower drug exposure target may be required in the neutropenic model. This could possibly be because of the lower inoculum used in this model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in our previous studies with azoles, we showed that using survival as a gold standard endpoint in our model provides useful exposure-response relationships. Studies with azoles in neutropenic (27,47,48) and nonneutropenic (23,49,50) models have shown that the exposure-response relationships are of the same order of magnitude; in fact, a slightly lower drug exposure target may be required in the neutropenic model. This could possibly be because of the lower inoculum used in this model.…”
Section: Discussionmentioning
confidence: 99%
“…There are only limited preclinical data on the in vivo efficacy of isavuconazole in azole-resistant IA (27). Therefore, the objective of the present study was to investigate the pharmacodynamics (PD) and dose-response and exposure-response relationships of isavuconazole against wild-type and clinical azole-resistant A. fumigatus isolates harboring different substitutions in the Cyp51A gene in an immunocompetent murine model of disseminated aspergillosis.…”
mentioning
confidence: 99%
“…However, there is a paucity of laboratory animal data for isavuconazole against Aspergillus spp. The pharmacodynamics of isavuconazole was explored in a murine neutropenic IPA model by Lepak and colleagues (15) and also in an invasive aspergillosis model of immunocompetent mice by Seyedmousavi et al (16). We therefore studied the efficacy and pharmacokinetics of isavuconazole in treatment of experimental IPA in persistently neutropenic rabbits.…”
mentioning
confidence: 99%
“…including Candida spp., Aspergillus spp., Cryptococcus spp., and mucormycetes (16)(17)(18)(19). The results of animal model studies have also shown that isavuconazole is effective in the treatment of invasive candidiasis, invasive aspergillosis, and mucormycosis (15,(20)(21)(22)(23). Moreover, in a recent phase 2 study, isavuconazole was shown to be well tolerated as prophylaxis in neutropenic patients with acute myeloid leukemia (31).…”
mentioning
confidence: 91%